Sources of growth and sorghum production trends in the Rio Grande do Sul, Brazil - Porto, Victor Hugo da Fonseca; Silveira Junior, Paulo (Pesquisa Agropecuaria Brasileira, 2014)
The objetive of this study was to quantify the influence of some sources of growth, such as area yield and localization effect, on the production of sorghum (Sorghum) and to evaluate the annual growth rate in the state of Rio Grande do Sul, Brazil, from 1973 to 1980. These sources of growth also were quantified for main nine microregions of this State, with the purpose to give a better understand of these sources of growth in the variation of sorghum production in Rio Grande do Sul State. In order to quantify these sources, a modified version of the model "Shift-share" was used, also known as structural diferentiation modal.